1997
DOI: 10.1007/bf02867953
|View full text |Cite
|
Sign up to set email alerts
|

Interference of anti-T3 autoantibodies in the measurement of total and free T3 in serum

Abstract: A case of anti-tdlodothyronine sutoantibodies is presented in this report. The thyroid hormone profile of a hypertensive patient, with multinodular goiter and history of exogenous thyroid hormone therapy, was found to be highly ambiguous. The total as well as free T3 levels were consistently high (out of range) whereas the T4 (total and flee) values were always within normal limits. The thyrotropin was found to be partially suppressed. Very low T3-Uptake indicated some kind of interference in the immunoassays.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Erregragui et al reported that autoantibodies against the hormone-forming site included in P3 peptide of thyroglobuline (12). Depending on the immunometric method being used these antibodies can result in free and total iodothyronine levels that are falsely high or low (4,5,6,7,13). In our patient, this led to the suspicion of TSH producing adenoma, RTH and resistance to TSH, all having been excluded by specific tests.…”
Section: Discussionmentioning
confidence: 83%
“…Erregragui et al reported that autoantibodies against the hormone-forming site included in P3 peptide of thyroglobuline (12). Depending on the immunometric method being used these antibodies can result in free and total iodothyronine levels that are falsely high or low (4,5,6,7,13). In our patient, this led to the suspicion of TSH producing adenoma, RTH and resistance to TSH, all having been excluded by specific tests.…”
Section: Discussionmentioning
confidence: 83%
“…The extremely high levels of serum FT4 in this patient can be explained by the presence of some interfering agent which appeared to compete with the antibodies used in the radioimmunoassay. The autoantibodies against thyroid hormones interfering in the RIA have been reported (3,4,8), but the binder reacting with radiolabelled T4 resulting in its precipitation could be any other serum protein also. The increased affinity/capacity of different plasma proteins particularly albumin has been reported as in familial dys-albuminemic hyperthyroidism(11).…”
Section: Resultsmentioning
confidence: 99%
“…Circulating antibodies to various thyroid antigens like thyroperoxidase, thyroglobulin, thyrotropin receptors and microsomal proteins may be found in various autoimmune thyroid disorders (1). Sometimes the autoantibodies may be generated against the thyroid hormones themselves (2,3,4). The incidence of anti-T3 or anti-T4 antibodies with varied specificity and dissociation constants in a euthyroid healthy population is about 1.8% (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, that is not fully understood at present. However, immune complexes with numerous serum bioactive substances have been also reported in recent years [135,[196][197][198][199][200][201][202][203][204][205][206][207][208]. For example, blood coagulation factor, various hormones (triiodothyroxine, thyroxine, chorionic gonadotropin, pituitary hormones and so on), vitamin B12, myocardial markers and so on complexed with immunoglobulin.…”
Section: Othersmentioning
confidence: 99%